Strategies of legitimation: MNEs and the adoption of CSR in response to host-country institutions - Rathert, Nikolas (Journal of International Business Studies, 2016)
Drawing on institutional theory, this study examines the question of how host country institutions affect corporate social responsibility (CSR) adoption by multinational enterprises (MNEs). I propose that CSR encompasses a set of practices that MNEs draw on to signal legitimacy in different kinds of institutional contexts – contexts that vary in how they shape issue salience and stakeholder power in a given issue field. Building on ideas related to field opacity and the managerial implications of CSR, I study why MNEs adopt two distinct types of CSR policies: standards-based CSR in response to contexts marked by issue salience, and rights-based CSR in response to contexts marked by stakeholder power. To test these hypotheses, I use subsidiary and firm-level data from a sample of 540 Western European MNEs in the issue field of labor rights. Results show that MNEs strategically adopt these CSR policies related to their presence in distinct institutional contexts. The study offers implications for how MNEs manage the legitimacy of their global operations and how CSR, as a form of private governance, can emerge as both a substitute and complement to regulatory institutions.